Starch extraction process coupled to protein recovery from leguminous tuberous roots (Pachyrhizus ahipa) - Diaz, Andrea (2016)
The objective of this work was to fit together the starch extraction from Pachyrhizus ahipa roots and the recovery of the proteins present in these storage organs, making an improved use of this novel raw material. The replacement of water by buffer PO4 −3/NaCl as solvent in the first extraction steps improved protein extraction without lowering the starch yield. The starches obtained from the traditional and the proposed methods exhibited some differences in appearance and technological and thermal properties, which were endorsed to the adjustment in the methodology of extraction rather than to the use of buffer as solvent. Thus, P. ahipa starch obtaining procedure could be coupled to protein extraction with a minimum change in the methodology. This innovation did not significantly shift the characteristics of the starch obtained and allowed to obtain a protein yield of 135.7 mg BSA equivalent protein/100 g of fresh roots.